ESTUDIO DE FACTIBILIDAD PARA LA CREACIÓN DE UNA EMPRESA DE PRODUCCIÓN DE MIEL DE ABEJA PARA EL CANTÓN GONZANAMÁ, PROVINCIA DE LOJA - Soto Briceño, Diego Ernesto (2016)
The thesis work entitled "Feasibility study for the creation of a production company of honey for the CANTON GONZANAMÁ, province of LOJA", was carried out with the purpose of choosing the title of engineer in banking and finance, which was carried out according to the rules of academic regime of the National University of Loja and to publicize the financial enterprise development and will serve as a basis for future decisions correct that take the administrative functioning of the same for which development it is based on both general and specific objectives. For the Foundation of the thesis, we used some methods and research techniques; among them we have method deductive, inductive, Analytical and synthetic and the techniques used were the survey, direct observation and literature collection. To comply with the first specific objective was carried out surveys which were directed to the families of the canton Gonzanamá place where will be marketed honey determining a sample which is 343 survey, which was obtained information relevant for the implementation of the project as the consumption of honey, to determine the per capita consumption , media most commonly used by the families for the implementation of the marketing plan and finally met the percentage of families will be use of the product, in terms of the offer was determined based on the surveys, i.e., the percentage mentioned that they would not make use of this product becomes demand satisfied fully by the bidders. The size of the company in regards to installed and used capacity was first established in the technical study, which concluded that it will be 780 liters of honey every four months a process that demand for 10.835 minutes and is externally 8 hours a day according to the current legislation, resulting in that used 6 capacity will be 100% of the installed is the proper location of the company is established using the method of location points and determined that it will be located in the district Luginuma of the Canton Gonzanamá, 2 km from the Centre of the canton via Cariamanga, barium Luginuma, in terms of the engineering of the project highlighted the biological assets, machinery, equipment and supplies needed for the proper functioning of the company He was the layout of the plant according to the measures of the ground for a good work of the staff. Study administrative, organizational and legal mentions that the company will be established as a joint-stock company, which has 6 members, base legal; i.e. their respective organizational charts and manuals necessary for the establishment and normal operation of the same, likewise details the necessary requirements to obtain the operating permit. The financial study determined the initial investment that is needed to operate the company with a total of $20.348,60, the VAN it will generate will be $51.418,09 positive being positive and acceptable, he has an IRR of 55,93% higher than the rate of opportunity, benefit cost ratio is greater than 1 gaining 0,70 cents gain, to recover the initial investment in 1 years 9 months 22 days and last indicator that is analysis sensitivity showed that the project supports a 50,70% increase in their costs, and a 29,84% decrease in revenues to not get negative net flows. The present work investigated shows positive results being this project both economic and socially feasible to run it since it contributes to the growth of economic development Canton Gonzanamá as Barrio Luginuma.